2018
DOI: 10.1097/scs.0000000000004709
|View full text |Cite
|
Sign up to set email alerts
|

Closure of Oroantral Fistula With Buccal Fat Pad Flap and Endoscopic Drainage of the Maxillary Sinus

Abstract: Oroantral fistula (OAF) is a pathologic communication between the oral cavity and the maxillary sinus. It is usually associated with maxillary sinusitis, where drainage of sinus infection is a mandatory step during closure of the fistula. The flap used for closure of OAF should be tension free, broadly based and well vascularized. The aim of this study was to assess the effectiveness of closure of OAF using buccal fat pad (BFP) flap with concomitant endoscopic middle meatal antrostomy for maxillary sinus drain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Local flaps are a group of surgical procedures for the treatment of small and moderate OAC/OAFs 19 and many studies described their clinical success. [20][21][22] However, current evidence did not support any superior technique. 2 A recent retrospective study reported similar outcomes in terms of closure success using either buccal flaps, palatal flaps, or buccal fat pad flaps.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Local flaps are a group of surgical procedures for the treatment of small and moderate OAC/OAFs 19 and many studies described their clinical success. [20][21][22] However, current evidence did not support any superior technique. 2 A recent retrospective study reported similar outcomes in terms of closure success using either buccal flaps, palatal flaps, or buccal fat pad flaps.…”
Section: Discussionmentioning
confidence: 66%
“…Local flaps are a group of surgical procedures for the treatment of small and moderate OAC/OAFs 19 and many studies described their clinical success. 2022…”
Section: Discussionmentioning
confidence: 99%
“…In two studies they reported that they treated 25 and 19 patients respectively for oroantral fistulas with the BB flap and had 100% success in closing the communication [2,12].…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA flow diagram was followed as illustrated in Figure 1 10 . The full text of nine publications was read and narrowed down to five eligible studies included in this review, covering a total of 86 OAFs 11–15 …”
Section: Methodsmentioning
confidence: 99%